Prevalence of vision threatening retinal conditions in patients referred for catract surgery from rural cataract camps: making the invisible visible - Sharma, Sandeep; Chaudhary, Prakhar; Tomar, Vijay Pratap Singh; Chaudhary, Richa Singh; Singh, Sindhuja; Jaiswal, Nikita; Gupta, Shraddha; Kumar, Abhinav (International Journal Of Community Medicine And Public Health, 2021)
Background: Cataract is the major cause of blindness in developing nations, in India it has been reported to be responsible for 50-80% of the bilaterally blindness in the country. Patients coming for community cataract surgery are being screened for retinal diseases which are third most blinding condition after cataract and glaucoma. Methods: This was a hospital based retrospective study. Patients included were of age between 40 to more than 80 years of age from 1st September to 31st December 2019. Comprehensive ocular and systemic examinations were done. Results: The age ranged from 40 to >80 years with a mean±SD age of 69.64±7.31 years. Mean±SD age of men was 69.98±7.37 years, and women were 69.36±7.26 years. Nearly half of the study subjects (48.5%) were between 60 and 69 years of age, whereas 3.9% were of 80 years and above. The prevalence of unilateral retinal disorders was 18.9% (95% CI: 17.2–20.8%), while bilateral retinal disorders was 33.5% (95% CI: 31.2–35.6%) The prevalence of retinal disorders was 45.47% between age 60–69 years, 54.48% between age 70–79 years, and 25% for age 80 years and above. Conclusions: Without screening programs, patients often fail to notice developing visual impairment until the disease progresses to advanced stage, especially in their nondominant eye. So community patients should also be screened for glaucoma and retinal diseases which are second and third most common blinding conditions in developing countries like India.